Mapping Potential Tourist Attractions in The Southern West Bandung Regency Area - Dicky Arsyul Salam (Journal of Tourism Sustainability, 2022)
West Bandung Regency is working hard to develop tourism in the southern region as a "sleeping and marginalized" area to become an up-and-coming destination for both domestic and foreign tourists. In addition to adopting the concept of territoriality, tourism planning in West Bandung Regency also applies an approach based on groupings of resources owned. In order to accelerate tourism development in the South West Bandung Regency area, this study seeks to convey the results of a study on mapping the potential for tourist attractions. An analytical tool in the form of a Point Rating System (PRS) is used to assess various aspects of tourism in these areas. Based on the analysis results, three areas of 3 different development priorities are revitalization of tourism destinations, development of tourism destinations, and pioneering tourism destinations. In conclusion, policy and regulatory aspects are very important in constructing the integrated tourism development of the Southern West Bandung Regency. Some aspects that need to be considered in development in the South West Bandung Regency include accessibility, connectivity, and infrastructure provision.